2022
DOI: 10.1021/acsnano.1c11221
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Yu–Shiba–Rusinov States and Inelastic Tunneling Spectroscopy for Intramolecule Magnetic Exchange Interaction Energy of Terbium Phthalocyanine (TbPc) Species Adsorbed on Superconductor NbSe2

Abstract: We investigated the spin properties of the terbium phthalocyanine (TbPc) species adsorbed on the superconductor NbSe 2 surface using scanning tunneling microscopy and spectroscopy. TbPc 2 is a molecule in a class of single-molecule magnets (SMMs), and the use of superconductor electrodes attracts attention for the application to the devices using the spin degree of freedom. TbPc is a building block of TbPc 2 and can reveal the spin component’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Consequently, it would be compelling to couple them with a preferred type of nanostructure, especially considering that studies have already demonstrated such coupling in the case of metallocene-SWCNT hybrids [ 228 ]. Here, the latest achievements by Komeda and co-workers, concerning the employment of superconducting NbSe substrates for TbPc molecules, are also worth mentioning, although the authors did not include information about the thickness of the used NbSe layer, which made it hard for us to consider it a nanostructure [ 229 , 230 ]. Nevertheless, the coupling of superconducting materials and SMMs seems to be a very appealing and promising route, the exploration of which should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it would be compelling to couple them with a preferred type of nanostructure, especially considering that studies have already demonstrated such coupling in the case of metallocene-SWCNT hybrids [ 228 ]. Here, the latest achievements by Komeda and co-workers, concerning the employment of superconducting NbSe substrates for TbPc molecules, are also worth mentioning, although the authors did not include information about the thickness of the used NbSe layer, which made it hard for us to consider it a nanostructure [ 229 , 230 ]. Nevertheless, the coupling of superconducting materials and SMMs seems to be a very appealing and promising route, the exploration of which should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…ii) Quantum gates iii) Chemical engineering of the Hamiltonian [ 7,8,13,30] [ [20][21][22][23] [ 27,31] iv) Quantum algorithms v) Embedded quantum error correction vi) Processability and hybrid structures [28] [ 17, [32][33][34] [ [35][36][37][38][39][40][41][42][43][44] Each column refers to a different achievement/capability. In the different rows, we report the experimental results/schemes, the related molecular structures, and the relevant references.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Copyright 2022, American Chemical Society). vi) Processability into hybrid structures and organization onto metallic and superconducting surfaces, [35][36][37][38][39][40] tuning their coupling with the substrate, while keeping their magnetic properties and enabling manipulation of electronic [41] and nuclear spins. [42] Color code for molecular structures: C gray; N pale blue, O red, S yellow, V purple, Cu orange, Ni and Cr blue, Tb cyan, lanthanides in (v) green and white.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations